2019
DOI: 10.1080/15592294.2019.1699695
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation following chemotherapy for breast cancer is associated with lack of memory improvement at one year

Abstract: The biological basis underlying cognitive dysfunction in women with early-stage breast cancer (BC) remains unclear, but could reflect gene expression changes that arise from the acquisition and long-term retention of soma-wide alterations in DNA methylation in response to chemotherapy. In this longitudinal study, we identified differences in peripheral methylation patterns present in women prior to treatment (T1) and 1 year after receiving chemotherapy (T4) and evaluated relationships among the differential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Lastly, increases in methylation ratios (as can be seen with gene ‘silencing’) were associated with lower memory scores one year after chemotherapy and with decreased memory scores from pre-to one year after post-chemotherapy, while no other domains (i.e. processing speed, attention and executive function) were found to be associated [22] .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Lastly, increases in methylation ratios (as can be seen with gene ‘silencing’) were associated with lower memory scores one year after chemotherapy and with decreased memory scores from pre-to one year after post-chemotherapy, while no other domains (i.e. processing speed, attention and executive function) were found to be associated [22] .…”
Section: Resultsmentioning
confidence: 86%
“…Changes in blood cells/proteins were also present, with decreases in G-CSF specifically [17] . Methylation ratios changed for 2199 CpG positions one year post-chemotherapy [22] .…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have demonstrated that primary breast cancer and/or its treatments significantly alter brain function and structure, it remains unclear how or why. Several studies, including our own, suggest genetic and/or epigenetic risk factors may play an important role (9,39,(65)(66)(67)(68)(69). However, these findings have been limited to the candidate variants selected and have shown some inconsistent results, which may relate to what brain regions were examined.…”
Section: Discussionmentioning
confidence: 89%
“…RPS6KA1 belongs to the family of the ribosomal protein S6 kinase (RPS6K) ( Li et al, 2012 ; Czaplinska et al, 2018 ). The RPS6K family is reported to be involved in a lot of pathways, which are important for tumor occurrence and progression ( Hajj et al, 2020 ; Lai et al, 2020 ; Yang et al, 2020 ). A new study indicates that RPS6KA1 is a potential target of new treatment strategies for drug-resistant AML patients with FLT3-ITD mutation, especially combining PI3K, PIM, or Bcl-2 family members ( Watanabe et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%